2004
DOI: 10.1080/03014460410001670120
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the early growth of twins and singletons

Abstract: The early growth of normal twins differs markedly from that of singletons. It is important to recognize that singleton reference values do not correctly reflect the growth of twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
8
46
0
1
Order By: Relevance
“…60 These differences may have their origin in prenatal conditions because compared with singleton pregnancies, twin pregnancies are characterized by earlier gestational age, lower birth weight and rapid catch-up growth, especially during the first year of life. 61 This mean difference in BMI between twins and singletons is, however, not a problem in twin studies because it can be taken into account in genetic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…60 These differences may have their origin in prenatal conditions because compared with singleton pregnancies, twin pregnancies are characterized by earlier gestational age, lower birth weight and rapid catch-up growth, especially during the first year of life. 61 This mean difference in BMI between twins and singletons is, however, not a problem in twin studies because it can be taken into account in genetic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous literature birth length was less reduced than birth weight when compared with singletons. 11,12 It is known from these studies that the fall off in birth length starts later in pregnancy and is of smaller magnitude than the fall off in birth weight. This may explain our findings that the deficit in height disappeared among 4-year-old twins, but they were still somewhat underweight.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies have shown that the differences in body size between twins and singletons at birth disappeared during childhood, but in a few studies differences remained until adulthood. [11][12][13][14][15] The Louisville Twin Study concluded that the effects of prenatal growth suppression on weight and height appeared to be fully dissipated by age 8, 11 and a Finnish study among 17-year-old twins reported that twins were as tall as singletons, but that boy twins were still leaner. 13 We found in a previous study that at the age of 5 years, female twins were as tall as singleton children, whereas male twins were still somewhat shorter than children in the general population.…”
mentioning
confidence: 99%
“…20 It is well known that twin pregnancies are different from singleton pregnancies and are characterized by earlier gestational age, lower birth weight and rapid catch-up growth, especially during the first year of life. 21 Birth weight discordance in both MZ and DZ twins is fairly common 22 and may be due to placental implantation and function resulting in nutritional imbalances between co-twins in the uterus. Because of the intra-uterine environmental constrains, MZ co-twins are less similar at birth than they would be based on their genetic potential.…”
Section: Genetics Of Relative Weight From Birth To Age 18 K Silventoimentioning
confidence: 99%